ORGANIZACYJNE CZYNNIKI WYPALENIA ZAWODOWEGO - Chirkowska-Smolak, Teresa (Wydział Prawa i Administracji UAM, 2009)
The professional burnout syndrome is a reaction to a long-time stress at work. It is a pathologically defensive reaction, a wrongful adaptation to stress. Explaining this phenomenon, the author emphasised the role of individual’s resources and competences of dealing with stress and heavy workload. The organisation’s resources, although mentioned in the paper, are less frequently analysed in detail. And yet, only a precise determination of the areas of incompatibility between the employees and the work ascertains creation of an effective programme of organisational intervention. The empirical study presented in the paper identifies organisational factors of professional burnout that affect persons in different jobs, not only social ones. The study incorporated a proposal developed by M. Leiter and C. Masłach that there are six work areas where dissonance may lead to professional burnout (work overload, control, remuneration, social relations, justice and values), and confirmed their role in the development of a burnout syndrome.
ORGANISATIONAL FACTORS OF PROFESSIONAL BURNOUT